Twelve’s Organic Pacet - Prahara, Rahma Sandhi; A’yuni, Diah Syifaul; Fauziah, Nur Dinah (Proceedings of Annual Conference for Muslim Scholars, 2025)
This study aims to analyze the implementation of a local economic model based on maqāṣid al-sharī‘ah in sustainable agriculture at Twelve’s Organic Pacet, focusing on community empowerment and environmental preservation. The model integrates spiritual, social, and ecological values through organic farming practices that emphasize not only economic benefits but also ḥifẓ al-bi’ah (environmental protection) and maṣlaḥah (collective well-being). The research adopts a qualitative approach using field observation, in-depth interviews, and documentation analysis. The findings reveal that the application of maqāṣid al-sharī‘ah principles is reflected in the adoption of fair-trade mechanisms, organic production processes, and participatory farmer training. However, challenges persist, such as limited literacy of maqāṣid al-sharī‘ah among local farmers, insufficient institutional collaboration, and lack of supportive public policy. Nevertheless, the growing global awareness of halal, sustainability, and social justice presents significant opportunities for developing Sharia-based agriculture. Theoretically, this research contributes to the development of Islamic economic thought by integrating maqāṣid al-sharī‘ah into sustainable agriculture. Practically, it offers an alternative model for policymakers to promote pesantren-based green economy initiatives and enriches the academic discourse on Islamic ecological economics.